Rosyjskie piśmiennictwo naukowe z zakresu przekładoznawstwa. Rzecz o monografii bibliograficznej Ewy Konefał pt. Przekładoznawstwo rosyjskie. T. 1: Autoreferaty dysertacji 1937–2015 (Wydawnictwo Uniwersytetu Gdańskiego, Gdańsk 2016) - Wojan, Katarzyna (Acta Polono-Ruthenica, 2018)
The article focuses on the state of academic literature in the field of Russian translation studies based on Ewa Konefał’s latest bibliographic monograph entitled Russian translation studies. Volume 1: Abstracts of dissertations 1937–2015 (Publishing house of Gdansk University, Gdansk 2016). The first part of the article justifies the need to create bibliographic monographs, and briefly presents Polish bibliographic research in Russian studies, with 169 publications from the years 1883–2016. In the main part of the article, the author discusses Konefał’s work and presents statistical data of documents from the field of Russian translation studies available in libraries in Russia and Post-Soviet countries based on Konefał’s research results. The total number of the excerpted titles of dissertations (PhD and postdoctoral) in the years 1937–2015 is 2202, with 87.5% belonging to the field of philology (1927 positions).